EFFECT OF DIFFERENT ECBOLIC THERAPY ON BLOOD METABOLIC PROFILE AND PROTEINOGRAM IN DYSTOCIA AFFECTED DANGI COWS - BHOI, D B; KHASATIYA, C T; DESAI, V K (The Indian Journal of Animal Reproduction, 2022)
The study was conducted on dystocia affected eighteen Dangi cows to investigate effect of different ecbolic therapies at calving on postpartum blood metabolic profile and proteinogram. Group-I (T1) and Group-II (T2) cows were injected intramuscularly with methyl-ergometrine (5mg) and dinoprost tromethamine (25 mg), respectively, immediately after parturition. Group-III (T3) cows received herbal ecbolic boli Exapar @ 2-4 boli, bid, PO for first 10 days postpartum. The mean plasma glucose levels were found significantly higher (P<0.05) on the day of calving and then declining up to 28th day postpartum. The mean serum total cholesterol levels in all treatment groups differed nonsignificantly with an increasing trend. The serum total protein concentrations fluctuated either significantly or nonsignificantly between various days of postpartum. The mean serum albumin concentration in T1 and T2 groups were decreased non-significantly (P?0.05) and in T3 group decreased significantly (P<0.05) at 7th day postpartum and thereafter linearly increased with a significant difference at 28th day postpartum. The mean serum globulin concentration in T1 and T3 groups decreased significantly (P<0.05) and in T2 group decreased non-significantly (P?0.05) at 7th day postpartum and thereafter linearly increased with significantly higher value at 28th day postpartum. The albumin globulin ratio fluctuated non-significantly (P?0.05) between different days/ intervals in all the treatment groups in Dangi cows and significantly (P<0.05) higher ratio was found on the 7th day postpartum in treatment T3.